2017
DOI: 10.1016/j.plantsci.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of small RNA populations in non-transgenic and aflatoxin-reducing-transformed peanut

Abstract: Power, Imana L.; Dang, Phat M.; Sobolev, Victor S.; Orner, Valerie; Powell, Joseph L.; Lamb, Marshall C.; and Arias, Renée S., "Characterization of small RNA populations in non-transgenic andaflatoxin-reducing-transformed peanut" (2017 t r a c tAflatoxin contamination is a major constraint in food production worldwide. In peanut (Arachis hypogaea L.), these toxic and carcinogenic aflatoxins are mainly produced by Aspergillus flavus Link and A. parasiticus Speare. The use of RNA interference (RNAi) is a promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 49 publications
(53 reference statements)
2
21
0
Order By: Relevance
“…Prominent among them is heterologous expression of foreign antifungal gene(s), either natural or synthetic, to provide resistance to the fungus and toxin production (Rajasekaran et al, 2005b;Ruhlman et al, 2014;Schubert et al, 2015;Sharma et al, in press). RNA-interference (RNAi)-mediated host induced gene silencing (HIGS) of key fungal genes critical for fungal pathogenesis and aflatoxin production has been successfully employed to incorporate A. flavus resistance in susceptible maize or peanut varieties (Arias et al, 2015;Bhatnagar-Mathur et al, 2015;Majumdar et al, 2017a;Masanga et al, 2015;Power et al, 2017;Sharma et al, in press;Thakare et al, 2017). HIGS technology does not require that the host plant express a foreign protein so food and feed produced from resistant lines of transgenic maize should be more acceptable to regulatory agencies and consumers.…”
Section: Molecular Breedingmentioning
confidence: 99%
“…Prominent among them is heterologous expression of foreign antifungal gene(s), either natural or synthetic, to provide resistance to the fungus and toxin production (Rajasekaran et al, 2005b;Ruhlman et al, 2014;Schubert et al, 2015;Sharma et al, in press). RNA-interference (RNAi)-mediated host induced gene silencing (HIGS) of key fungal genes critical for fungal pathogenesis and aflatoxin production has been successfully employed to incorporate A. flavus resistance in susceptible maize or peanut varieties (Arias et al, 2015;Bhatnagar-Mathur et al, 2015;Majumdar et al, 2017a;Masanga et al, 2015;Power et al, 2017;Sharma et al, in press;Thakare et al, 2017). HIGS technology does not require that the host plant express a foreign protein so food and feed produced from resistant lines of transgenic maize should be more acceptable to regulatory agencies and consumers.…”
Section: Molecular Breedingmentioning
confidence: 99%
“…The same group working on peanuts more recently presented evidence that “89 known and 10 novel miRNAs were differentially expressed in the transformed peanut lines. Two small interfering RNAs derived from the inverted repeat, and 39 siRNAs mapped without mismatch to the genome of A. flavus were present only in the infected transformed lines” . Only two of the five genes targeted in the aflatoxin‐suppressing construct were identified among the siRNAs produced, the ones targeting the polyketide synthase and the aflS / aflJ controlling element.…”
Section: The Evolution Of Increased Efficacy Of Host‐induced Gene Silmentioning
confidence: 99%
“…It was already questioned a few years ago whether essentially dormant seeds could produce the RNAi necessary to suppress mycotoxin production from post‐harvest infection . The data showing that aflatoxin biosynthesis is not sufficiently suppressed in late stage maturing peanut seeds implies that it will be even less effective in drier seed, suggesting that aflatoxin will be produced post‐harvest in poorly stored grain despite the crop being transformed for HIGS. Can HIGS be used to suppress fungal growth of most or all aflatoxin producing Aspergillus species using consensus sequences to drive HIGS? HIGS has had a modicum of success in suppressing many other fungi and oomycetes on a variety of crops (some examples are given in Table ) and it is a wonder that this approach has not been used with Aspergillus , to the best of our knowledge.…”
Section: Questions About the Utility Of The Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Lavkor et al [9] reported that A. flavus NRRL21882 (Afla-guard) was applied in three different ways in trial experiment, and it reduced aflatoxin amount varying from 98.4% to 99.8% and suppressed aflatoxin contamination of peanuts [9]. In another research, Power et al [33] used the method of RNA interference (RNAi) as a promising method to reduce or prevent the accumulation of aflatoxin in peanut seed. In this study, they also performed highthroughput sequencing of small RNA populations in a control line and in two transformed peanut lines that expressed an inverted repeat targeting five genes involved in the aflatoxin biosynthesis pathway and that showed up to 100% less aflatoxin B 1 than the control samples.…”
Section: Soil Typementioning
confidence: 99%